Preliminary evidence for a serum disaccharide signature of invasive Candida albicans infection detected by MALDI Mass Spectrometry. (January 2015) - Sendid, B.; Poissy, J.; François, N.; Mery, A.; Courtecuisse, S.; Krzewinski, F.; Jawhara, S.; Guerardel, Y.; Poulain, D.
Abstract: The diagnosis of systemic Candida infections is a recognized challenge. We developed a mass spectrometry strategy to detect signals from Candida molecules in patients' sera. Pre-analytical procedures were designed to extract oligosaccharides from serum. A peak m / z of at 365 was specifically revealed in sera from patients with candidaemia with regard to healthy controls. This biomarker was identified as a disaccharide, its presence did not correlate with mannanaemia or glucanaemia. Mouse models of Candida albicans colonization and infection showed that the signal was specifically associated with tissue invasion, suggesting that clinical evaluation of its usefulness in discriminating colonized and infected patients would be worthwhile.